(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2017)
The information contained in this article seeks to raise awareness of the environmental pollution generated by the immeasurable growth of construction projects; from an academic exercise that aims to evaluate the environmental impact produced by a work of low magnitude. Therefore, it is necessary to carry out a methodology that involves defining the baseline, describing the phases and activities, establishing the checklist, evaluating the Leopold matrix and, finally, proposing mitigation strategies as a thematic result of the research. To this is added the reflection that accompanies the process, from an analytical, interpretative or critical perspective that highlights the importance of putting this type of research into practice for any